Microfluidic‐Spinning‐Directed Microreactors Toward Generation of Multiple Nanocrystals Loaded Anisotropic Fluorescent Microfibers. (5th November 2015) - Zhang, Yan; Wang, Cai‐Feng; Chen, Li; Chen, Su; Ryan, Anthony J.
Abstract : Anisotropic fluorescent hybrid microfibers with distinct optical properties and delicate architectures have aroused special interest because of their potential applications in tissue engineering, drug delivery, sensors, and functional textiles. Microfluidic systems have provided an ideal microreactor platform to produce anisotropic fibers due to their simplified manipulation, high efficiency, flexible controllability, and environmental‐friendly chemical process. Here a novel microfiber reactor based on a microfluidic spinning technique for in situ fabrication of nanocrystals loaded anisotropic fluorescent hybrid microfibers is demonstrated. Multiple nanocrystal reactions are carried out in coaxial flow‐based microdevices with different geometric features, and various nanocrystals loaded microfibers with solid, string‐of‐beads and Janus topographies are obtained. Moreover, the resulted anisotropic fluorescent hybrid microfibers present multiple optical signals. This strategy contributes a facile and environmental‐friendly route to anisotropic fluorescent hybrid microfibers and might open a promising avenue to multiplex optical sensing materials. Abstract : A fiber microreactor based on a microfluidic spinning technique is proposed for the in situ fabrication of nanocrystals loaded anisotropic fluorescent hybrid microfibers. By designing coaxial flow microdevices with different geometric features, multiple nanocrystal reactions in microreactors result in microfibers with delicate topographies and distinct optical properties. This work develops a facile platform for rapid fabrication of anisotropic fluorescent hybrid microfibers.